Tsingtao Brewery Company Ltd. - He, Ke (Coca) (Animo Repository, 2007)
The Chinese alcoholic beverage market has grown at an astounding pace in recent years, spurred on by the massive levels of foreign investment in the market, along with the rise in the average levels of consumer spending in China. China has now overtaken the US to become the largest national alcoholic beverage market in the world. With total revenues of $45.7 billion in 2006 and an anticipated compound annual growth rate (CAGR) of 4.7% for the five-year period 2006-2011, alcoholic beverage market in China deserves to be understood more clearly. TSINGTAO Brewery Company Ltd which based in Shandong province in China is now China's largest brewer by output. The company is involved in the manufacturing and distribution of beer and related businesses. TSINGTAO, of which 30.6% is owned by the Chinese government, is also the largest beer exporter in China. Its flagship brand, TSINGTAO Beer, is the best selling Chinese beer in the US. Its two major domestic brands, TSINGTAO LARGE and PURE DRAFT represents highest quality beer in Chinese alcoholic beverage market. This paper consists of a thorough analysis of external and internal environment. It has indicated the Threats and the Opportunities to the alcoholic beverage industry; Strengths and the Weaknesses of TSINGTAO; Broader Societal Expectations; and Personal Values of Key Implementers. By analyzing this four dimensions following Michael Porters Competitive Strategy framework, this paper includes two proposed corporate strategies for TSINGTAO. These two strategies are: Strategy #1: Gradually phase out low performing low-end brands. Strategy #2: Expand target market by creating market niches in customer segments which are currently not being served by competitors such as female alcoholic beverage drinker. For the proposed strategies to be better executed and implemented, this paper recommended detailed plans based on McKinsey 7-S framework and the eight Strategy Implementing Tasks or called the 8-SIT framework.